Studi Tidak Tercapainya Temperature Secara Optimal pada Mesin Pendingin (Refrigerator) di Kapal MT. Kuang - Fakhrozi, Rizal Fahmi; Darmana, Eka; Wilastari, Santhi (Marine Science and Technology Journal, 2024)
A refrigeration machine is a device used to transfer heat from indoors to outdoors to make the temperature of the room lower with the aim of cooling/preserving food. Cooling machines on MT ships. Kuang, when the ship was sailing, experienced that the optimal temperature was not reached, so it was necessary to observe this problem. So that action can be taken so that similar problems can be resolved and do not happen again. This research is based on a case study conducted on the MT ship. Kuang. The method that the author uses in collecting data is the observation method, namely a data collection method by making direct observations of the research object, an interview method with the author communicating with technicians regarding the problem being handled, as well as a literature study method, namely collecting references contained in relevant books, journals and studies. Approach to problem analysis using a qualitative descriptive method. From the results of the discussion carried out by the author, it is known that the optimal temperature was not achieved due to freon leaks in the evaporator pipe, dirty oil separator, dirty condenser and sea chest, and the cooling machine door not being tight. This is the impact of lack of maintenance on the cooling machine (refrigerator) and the cooling machine is quite old.